Analysis of non-destructive testing ultrasonic signal for detection of defective materials based on the Simulink Matlab Mathematica computation method - Ade Febrianti; Muhammad Hamdi; Juandi Muhammad (Lembaga Studi Pendidikan dan Rekayasa Alam Riau, 2021)
In this paper, an ultrasonic non-destructive test (NDT-UT) has been carried out on steel using the Simulink-MATLAB Mathematica computation method. This study aims to analyze the NDT-UT output signal for material defect detection using secondary data as the first sample. The sample is then analyzed using the fast Fourier transform (FFT) method to produce a spectrum waveform and image thermography. It can be seen that there is a decrease in signal height from 1 a.u to 0.55 a.u. The first sample waveforms were used to analyze the second sample, third sample, and fourth sample, and all the samples had different defects. The results of the sample analysis are in the form of a thermographic image that shows the temperature level based on the distribution of red (R), green (G), and blue (B) images on the sample surface. The NDT-UT output signal produces a sinusoidal wave similar to the results of the Simulink-MATLAB modeling analysis on the initial input echoes and the back wall, with a percentage inequality of 10%. Then validated the sinusoidal signal from the NDT-UT which gave a percentage of inequality between 0% – 42%. More complex or irregular defects result in a larger percentage or vice versa.